Peran Dinas Koperasi, Perindustrian, dan Perdagangan dalam Pemberdayaan UMKM Tenun Ikat di Kabupaten Nagekeo - Maria Stella Maris Muke Samu; Made Ngurah Demi Andayana; Adriana Rodina Fallo; Marthina Raga Lay (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting economic growth and improving community welfare, particularly at the regional level. In Nagekeo Regency, the ikat weaving craft sector represents an important local economic potential that also carries significant cultural value. However, weaving entrepreneurs still face several challenges, including limited business capital, restricted market access, and low utilization of digital technology for product marketing. This study aims to analyze the role of the Department of Cooperatives, Industry, and Trade of Nagekeo Regency in empowering MSME actors, particularly ikat weaving groups. The research employs a qualitative approach with a descriptive research design. The study involved 18 informants consisting of local government officials, MSME actors, and institutional partners selected through purposive sampling. Data collection techniques included observation, in-depth interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the department performs facilitative, educative, and technical roles in empowering weaving groups through production training, digital marketing assistance, provision of business facilities, and technical guidance on product innovation. These programs contribute to improving weavers’ skills, product quality, and market opportunities, although their implementation still faces limitations related to budget constraints and uneven program coverage.